Association of maximal systolic blood pressure with poor outcome in patients with hyperattenuated lesions on immediate NCCT after mechanical thrombectomy. (25th June 2019) - Ding, Xinfa; Xu, Chao; Zhong, Wansi; Gong, Xiaoxian; Zhou, Ying; Chen, Zhicai; Lou, Min
Abstract : Background and purpose: This study aimed to investigate the relationship between blood pressure ( BP) management and clinical outcome in patients with hyperattenuated lesions on non-contrast CT (NCCT) immediately after mechanical thrombectomy (MT). Methods: We retrospectively reviewed our prospectively collected cohort for consecutive patients with acute ischemic stroke (AIS) who received MT between October 2013 and July 2018. Hourly systolic BP (SBP) and diastolic BP (DBP) values were recorded for 24 hours following MT, and then maximum SBP (SBPmax ) and DBP (DBPmax ) values were identified. Poor outcome was defined as 3-month modified Rankin score (mRS) 3–6 and parenchymal hemorrhage (PH) was defined according to the European Cooperative Acute Stroke Study (ECASS) II trial. Associations of BP parameters with poor outcome and PH were determined using binary logistic regression models. Receiver operating characteristics (ROC) curve analysis was used to determine the predictive value of BP. Results: Initially 262 patients with AIS who received MT were reviewed and 148 patients with hyperattenuated lesions on immediate NCCT were enrolled in the final cohort for analysis. Binary logistic regression showed that every 10 mm Hg increase in SBPmax was independently associated with a poor outcome (OR 1.426; 95% CI 1.095 to 1.855; p=0.008) and PH (OR 1.025; 95% CI 1.005 to 1.480; p=0.044). SBP ≤140 mm Hg during the post-procedural 24-hour period was associated with lower odds of a poor outcome and PH compared with the other group. Conclusions: Control of maximal SBP within 24 hours might be related to a low rate of PH and poor outcome in patients with hyperattenuated lesions on immediate NCCT after intervention.